دبستان فراہی کی تفاسیر پر تنقیدات:تجزیاتی مطالعہ: Analytical Study of Criticism on Farahi’s Schol of Thought - Zafar Iqbal (MEI, 2023)
In subcontinent there are many exegeses school of thoughts. One of them is Farahi’s school of Thought. Its founder was Hamid ud Din Farahi. He belongs to Indian district Uterperdaish. His exegeses principles are different from traditional. So, his exegesis based on his own developed principles is completely have different approach. In this regard, he had not only diverted from traditional trend but also have a new approach. For example, in the exegesis of Surah Kausar, he did not accept the traditional explanation of Kausar river in heaven. He said it is Bait ullah already exist in this world. In this type of his elucidations, he and his school of thought faced criticism. Another main personality of this school of thought is Molana Amin Ahsan Islahi. There are about more than ten written criticisms exists on exegesis of Farahi’s school. These criticisms are of two types, on their principles of exegeses and direct on their exegesis.